Perancangan Geometri Jalan Rel Kereta Api Cepat Surabaya – Jakarta Berdasarkan Jalur Eksisting Stasiun Pasar Turi – Stasiun Lamongan (KM. 0+000 – KM. 41+046) - Cahya Rafiyoga Harnan; Nugroho Utomo; Aulia Dewi Fatikasari (Universitas Batanghari Jambi, 2026)
Trains have become a reliable mode of land transportation as they can avoid traffic congestion, operate on structured schedules, and offer high passenger and freight capacity. Technological advancements have led to the development of high-speed trains capable of traveling over 300 km/h on dedicated, unobstructed tracks, enhancing travel efficiency and regional connectivity. In Indonesia, the Jakarta–Surabaya high-speed rail project is expected to facilitate mobility, reduce congestion on the Pantura corridor, and complement conventional lines such as the Pasar Turi–Lamongan route. This study aims to analyze the horizontal and vertical alignment design, rail elevation dimensions, and the location of gradient transitions on the high-speed rail line between Pasar Turi and Lamongan stations. The geometric planning of the high-speed rail uses references from Minister of Transportation Regulation No. 7 of 2022 and the book Jalan Rel by Suryo Hapsoro Tri Utomo, with secondary topographic data from Google Earth Pro processed using Global Mapper and Civil 3D. The results indicate that the horizontal alignment is designed with speeds below 350 km/h—specifically 300 km/h, 250 km/h, and 120 km/h—to avoid overlap in closely spaced curves, while the vertical alignment is planned for a design speed of 350 km/h with concave and convex vertical radii of 25,000 meters and a gradient of less than 2%. The study concludes with a rail elevation of 175 mm, curve radii of 8,000 meters for 350 km/h, eight SCS-type curves with some lower-speed segments to prevent spiral overlap, and a vertical alignment on an elevated track with eight curve points, a radius of 25,000 meters, and a maximum gradient of 2%.